A novel trapezoidal intuitionistic fuzzy information axiom approach: An application to multicriteria landfill site selection. (January 2018) - Kahraman, Cengiz; Cebi, Selcuk; Onar, Sezi Cevik; Oztaysi, Basar
Abstract: Information axiom is used to determine the best option among the potential alternatives. In case of uncertain parameters, information axiom has been extended to its ordinary fuzzy versions in the literature. In this paper, we developed a trapezoidal intuitionistic fuzzy information axiom model in order to handle the hesitancy of experts. The developed model aggregates the judgments of more than one expert and proposes a new defuzzification method for trapezoidal intuitionistic fuzzy sets. Our model was applied to a multicriteria landfill site selection problem and a sensitivity analysis was conducted to check the robustness of the given decisions.